Hyalomma aegyptium as dominant tick in tortoises of the genus Testudo in Balkan countries, with notes on its host preferences - Siroký, Pavel; Petrzelková, Klára J; Kamler, Martin; Mihalca, Andrei D; Modrý, David (Experimental & applied acarology, 2006)
Collection of 1327 ticks sampled throughout Greece, Bulgaria, Romania and Croatia, from 211 tortoises belonging to three species, Testudo marginata Schoepff, T. graeca Linnaeus, and T. hermanni Gmelin, revealed the presence of four species of ixodid ticks, namely Hyalomma aegyptium (Linnaeus), Haemaphysalis sulcata Canestrini and Fanzago, H. inermis Birula and Rhipicephalus sanguineus (Latreille). Study confirmed the strong dominance of all life stages of H. aegyptium among ticks parasitizing west Palaearctic tortoises of genus Testudo Linnaeus. Furthermore, a considerable portion of ticks collected from tortoises in southwestern Bulgaria represent larvae and nymphs of H. sulcata. At the same area we collected as exception one larva and one nymph of H. inermis from a single specimen of T. hermanni. Our findings of four adults of R. sanguineus is the first record of this species from reptilian host. According to our results achieved on localities with syntopic occurrence of two tortoise species, T. marginata and T. graeca represent in the Balkans the principal hosts of H. aegyptium, whereas T. hermanni serves only as an alternative host in the areas close to range of either T. marginata or T. graeca.
Keywords: želvy; prevalence; Ixodidae; Male; infestace klíšťaty; Tick Infestations; Řecko; Host-Parasite Interactions; neparametrická statistika; Greece; interakce hostitele a parazita; Animals; Turtles; Statistics, Nonparametric; zvířata; mužské pohlaví; Prevalence; ženské pohlaví; Female; Europe, Eastern; východní Evropa